The Intervening Factors of Evidence-Based Educational Policy in the Education and Promotion of Students' Health and Their Evaluation from the Point of View of Experts: A Mixed Study - Parisa Mohammadi; Behnam Talebi; Mahasti Alizadeh (Taṣvīr-i salāmat)
Background. The use of evidence-based policymaking in education policy and student health promotion can enhance the precision and reliability of policies. The current study aimed to identify the intervening factors of evidence-based educational policy and the possibility of improving them in the education and promotion of students' health. Methods. The current study employed a mixed-methods design, combining qualitative and quantitative approaches, utilizing thematic analysis and survey methods. In 2022, the study began by exploring the perceptions of experts and policymakers through semi-structured interviews with 18 participants. In the next step, a questionnaire was administered to 366 school principals to assess the extent to which intervening factors in the education system can be addressed. The qualitative phase employed a purposeful sampling method, while the quantitative phase utilized proportional random sampling. In order to ensure the accuracy of information in the qualitative phase, triangulation method was used, and in the quantitative phase, data model fit evaluation was conducted using first-order and second-order confirmatory factor analyses. Qualitative data analysis was done using Esterberg's thematic analysis method, and quantitative data was done using a one-sample t-test. Results. Based on the themes extracted from the research, the obstacles of evidence-based educational policymaking in the education and health promotion of students included a lack of dynamism of research policy and evidence collection, a lack of political decision-making, resource limitations, the evidence-policy gap, a lack of science uptake, and the possibility of paying attention to each of them in the educational system, which is regarded above average. Conclusion. The effective application of evidence-based educational policy requires attitudinal changes at the higher and macro levels of the educational system and health education.